Identifikasi Peran Modal Sosial Terhadap Tingkat Kesejahteraan Pelaku Industri Rumahan Sepatu Bayi di Desa Sukadamai - Farina Ekarini; Sugeng Heri suseno (Jurnal Pusat Inovasi Masyarakat (PIM), 2020)
The home industry is a form of business activity to create a level of community welfare. Inpractice, every baby shoe industry has its way of developing its business. The role of social capital isconsidered as an important part to know how the process of transfer of knowledge obtained by thebaby shoe industry and to analyze the history and constraints that have been felt by the businessmanof baby shoe industry. Therefore, this study aims to identify the role of social capital in the welfarelevel of the baby shoe industry. The method in this research was carried out in a descriptivequalitative manner, interview techniques. The results showed that the role of social capital carriedout by the businessman of baby shoe industry is bounding, bridging, and linking. The analysis showsthat they have a high level of trust and are compliant with social norms, have a fairly good level ofnetwork and participation in, and have a high level of dependency with baby shoe handkerchief.The role of social capital carried out by the businessman as an effort to improve their welfare. Themovement showed the businessman of baby shoe industry made the Sukadamai village known asthe baby shoe craftsman village.